Updated Detailed Review of Trachyspermum Ammi: Composition, Applications and Pharmacological Profile: Pharmaceutical Science-Pharmacy - Nabi, Kamal; Imanshu; Swarup, Saswat; Bhatia, Deepika; Bhatti, Manisha; Singh, Lovedeep (International Journal of Life Science and Pharma Research, 2023)
Trachyspermum Ammi (T. Ammi) is a traditional medicinal plant belonging to the family Apiaceae. It, also known asAjacine or Ajwain, is an herb with Egyptian origins. It is distributed all over India and mainly cultivated in Rajasthan and Gujarat.This review is designed to discuss the updated pharmacological activities of T. Ammi, its phytochemistry, herbal formulations,and patents filed on its novel formulations and their actions. Until now, no such review has discussed the above mentionedparticulars on the same platform. The review aims to provide the updated traditional and pharmacological activities of T. Ammi,along with its phytochemistry, herbal formulations, and microwave-assisted extraction method. The microwave-assistedextraction method is less time-consuming, cost-effective, and gives more extractive value than other methods. We have alsoadded the latest novel patents of the T.ammi. It is an annual plant with tall growth that is fragrant and bears white blooms andlittle brownish berries, small, grey, bitter, and peppery. The seeds or fruit of this plant are the parts that are used mostfrequently. Ajwain’s fruits have 5% essential oil in them. Ancient researchers highly influenced the use of this herb. The essentialoil brings on Ajwain’s aroma and flavor. Ajwain is a potent traditional medicine that is frequently used to cure a variety ofillnesses in both humans and animals. To include literature evidence to support the article’s theme, a search was performed onfive electronic databases, including PubMed, Scopus, Web of Science, Embase, and Google Scholar, by using specific keywords.